Prevention of Transmission of Zika Virus at Point of Entries - Experience from International Airport, Mumbai - Amitabha, Dan; Mohd. Jalaluddeen, Pasi A. R., Khandare K. P.,; Singh, Sujeet Kumar (International Journal of Innovative Research in Medical Science, 2016)
Introduction: Zika virus is a mosquito borne flavivirus. It is transmitted by the bite of the Aedes Aegypti mosquito. In July 2015 Brazil reported an association between Zika virus infection and Gullain-Barre syndrome. In October 2015 Brazil reported an association between Zika virus infection and microcephaly. Considering the gravity of the situation, WHO has declared Zika virus disease to be a Public Health Emergency of International concern (PHEIC) on 1st February 2016. Objective: To analyse/look through how well the PHEIC situation was managed at Mumbai Airport and problem faced if any. Methods: Data available at APHO Mumbai from 1.2.2016 to 30.10.2016 was analysed. Information was collected by interviewing representatives of APHO, FRRO, CISF, Airport Manager and Airline Operators. Results: During the study period a total of 2833244 international passengers arrived at C S I Airport. Out of 2833244 international passengers 31369 (1.1%) were from Zika affected countries. There was good Intersectoral coordination between Airport Authority, Local government, Nodal officer of Point of Entry and other stakeholders. Conclusion: APHO, Mumbai has shown the capacity to detect, assess, report and respond to Zika PHEIC as per IHR 2005.